Exploring ChatGPT and Higher Education Practice in Indonesia - ., Yusuf; ., Hudaya; Abdu, Wamaungo Juma (International Journal of Membrane Science and Technology, 2023)
The rapid advancement of artificial intelligence (AI) technologies has brought about disruptive changes in various industries, including higher education. Among these transformative technologies, ChatGPT has emerged as a powerful tool that has captured the attention and enthusiasm of students in higher education institutions. While students embrace this AI-based tool, educators find themselves in a state of unease, unsure of how to navigate the uncharted territory of integrating such technologies into their teaching practices. In Indonesia, a country that has witnessed previous technological disruptions in higher education, the introduction of AI technologies, particularly ChatGPT, has placed practitioners in a dilemma regarding the best course of action. This concept note proposes a research study to explore the possibility of the proper use of AI technologies, such as ChatGPT, in higher education practice in Indonesia.